(untitled) (Repertorio Científico, 2020)
ABSTRACT: Necrosis Pancreatic Infectious Virus does not block 701-STAT1 (α/β) tyrosine in Oncorhynchus mykiss (‎Salmoniformes: ‎Salmonidae). Introduction: Infectious pancreatic necrosis virus (IPNV) is a pathogen important that affects predominantly salmonids. The type I interferon alpha system has a crucial role in the first line of defense against IPNV infection. IFN-I(α) activation triggers the signaling pathway JAK-STAT, binding to their receptors results in the rapid phosphorylation of STATs a critical step for the nuclear translocation to induce the interferon stimulated genes (ISGs). The relationship between infectivity level of IPNV strain and pathway signaling of IFN is yet poorly understood. Objective: our purpose was to investigate if the IFN-I(α) signaling pathway is affected by IPNV strains of different infectivity levels. Methods: We used two IPNV isolated (VR-299 and Sp) to infect RTG-2 cells. Total RNA was isolated using the commercial kit for determine to VP2 expression and ISGs using qRT-PCR. Western Immunoblotting analysis was carried out for determine the 701 STAT1(α/β) phosphorylation into infected cells. Results: Hence, a higher virulence strain is not associated with a greater blocking effect for interferon signaling. Furthermore, the activation of Y701-STAT1 (α/β) was significantly increased in serotype Sp virus infected cells compared with serotype VR-299 virus infected cells, indicating that IPNV inhibits IFN signaling pathway. Conclusions: As concluded, IPNV does not block the phosphorylation of 701-tyrosine STAT1 (α/β) stimulated by IFN-I(α), contrary to other RNA viruses.